Sequence analysis on the mitochondrial COXI gene of recent clinical isolates of Plasmodium knowlesi in Klang valley, peninsular Malaysia - Fong, Mun Yik; Lau, Yee Ling; Chin, Lit Chien; Al-Mekhlafi, A.M.Q. (Malaysian Society of Parasitology and Tropical Medicine, 2011)
The cytochrome oxidase subunit I (COXI) gene sequences of three recent (20072008) clinical Plasmodium knowlesi isolates from Klang Valley, peninsular Malaysia, were determined and compared with those of older (1960's) peninsular Malaysia, recent isolates from Sarawak (on Borneo Island), and an isolate from Thailand. Multiple alignment of the sequences showed that the three clinical isolates were more similar to the older peninsular Malaysia isolates than to those from Sarawak and Thailand. Phylogenetic tree based on the COXI sequences revealed three distinct clusters of P. knowlesi. The first cluster consisted of isolates from peninsular Malaysia, the second consisted of Sarawak isolates and the third composed of the Thailand isolate. The findings of this study highlight the usefulness of mitochondrial COXI gene as a suitable marker for phylogeographic studies of P. knowlesi.